Infrared Video Pupillography Coupled with Smart Phone LED for Measurement of Pupillary Light Reflex - Chang, Lily Yu-Li; Turuwhenua, Jason; Qu, Tian Yuan; Black, Joanna M.; Acosta, Monica L. (Frontiers in Integrative Neuroscience, 2017)
Clinical assessment of pupil appearance and pupillary light reflex (PLR) may inform us the integrity of the autonomic nervous system (ANS). Current clinical pupil assessment is limited to qualitative examination, and relies on clinical judgment. Infrared (IR) video pupillography combined with image processing software offer the possibility of recording quantitative parameters. In this study we describe an IR video pupillography set-up intended for human and animal testing. As part of the validation, resting pupil diameter was measured in human subjects using the NeurOpticsTM (Irvine, CA, USA) pupillometer, to compare against that measured by our IR video pupillography set–up, and PLR was assessed in guinea pigs. The set-up consisted of a smart phone with a light emitting diode (LED) strobe light (0.2s light ON, 5s light OFF cycles) as the stimulus and an IR camera to record pupil kinetics. The consensual response was recorded, and the video recording was processed using a custom MATLAB program. The parameters assessed were resting pupil diameter, constriction velocity, percentage constriction ratio, re-dilation velocity, and percentage re-dilation ratio. We report that the IR video pupillography set-up provided comparable results as the NeurOpticsTM pupillometer in human subjects, and was able to detect larger resting pupil size in juvenile male guinea pigs compared to juvenile female guinea pigs. At juvenile age male guinea pigs also had stronger pupil kinetics for both pupil constriction and dilation. Furthermore, our IR video pupillography set-up was able to detect an age-specific increase in pupil diameter (female guinea pigs only) and reduction in constriction velocity (male and female guinea pigs) as animals developed from juvenile (3 months) to adult age (7 months). This technique demonstrated accurate and quantitative assessment of pupil parameters, and may provide the foundation for further development of an integrated system useful for clinical applications.